Empowering Adolescents: Cultivating Holistic Growth for Success - Kumar, Vikas; Bahadur, Vir Bahadur (Integrated Journal for Research in Arts and Humanities, 2024)
One of the most important stages of human development, adolescence, is full of opportunity for significant change. Education serves as a catalyst during this time of self-discovery, going beyond the limitations of typical academic settings. Taking center stage is holistic education, which recognizes the complex interplay between the intellectual, emotional, physical, social, and moral facets that shape the development of adolescents. This essay explores the essential elements of holistic education and the need to go beyond conventional educational paradigms in order to highlight the importance of empowering teenagers through this kind of education. It promotes adopting thorough evaluations that go beyond simple grades, embracing experiential learning techniques, and incorporating life skills education into academic courses. The study also explores the obstacles to holistic education implementation, such as standardized testing demands, budget constraints, and deeply ingrained reluctance to change in established educational systems.